Humor, seriously : why humor is a secret weapon in business and life and how anyone can harness it. Even you. - Aaker, Jennifer Lynn; Bagdonas, Naomi (New York : Currency, 2021)
"Many people understand humor's power intuitively. But when it comes to using it with intention, far fewer know how. As a result, humor is vastly underleveraged in most workplaces today, impacting our performance, relationships, and health, and contributing to a permanent and unsightly frown known as "resting boss face." In fact, research shows that humor is one of the most powerful tools we have for accomplishing serious things. Top executives know this, which is why 98 percent prefer employees with a sense of humor, and 84 percent believe these employees do better work. Studies show that humor makes us appear more competent and confident, strengthens relationships, unlocks creativity, and boosts our resilience during difficult times."--
Foreword: Humor makes us human / Ed Catmuyll -- Gravity and levity -- The humor cliff -- This is your brain on humor -- The anatomy of funny -- Putting your funny to work -- Leading with humor -- Creating a culture of levity -- Navigating the gray areas of humor -- A secret weapon in life -- (After)words: A conversation with Michael Lewis.
Includes bibliographical references (pages 239-246) and index.
Keywords: Wit and humor -- Psychological aspects; Laughter; Management -- Psychological aspects; Organizational behavior